2021
DOI: 10.1002/ange.202106881
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent CH–π and π–π Interactions in Phosphoramidite Palladium(II) Complexes with Strong Conformational Preference

Abstract: The weak noncovalent interactions and flexibility of ligands play ak ey role in enantioselective metal-catalyzed reactions.I nt ransition metal complexes and their catalytic applications,the experimental assessment and the design of key interactions is as difficult as the prediction of the enantioselectivities,e specially for flexible,p rivileged ligands such as chiral phosphoramidites.T herefore,t he interligand interactions in cis-Pd II L 2 Cl 2 phosphoramidite complexes were investigated by NMR spectroscopy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…Sorption by electrostatic interaction depends on the pH of the solution and the point of zero charge (PZC) of the sorbent [199]. Modelling studies have shown that π-π interactions and H-bonding interactions play an important role in the sorption of PAHs (polycyclic aromatic hydrocarbons) [200][201][202][203]. π-π interactions are weak non-covalent interactions that influence the chemical structure by providing significant stabilisation and strengthening of the bonds.…”
Section: Sorptionmentioning
confidence: 99%
“…Sorption by electrostatic interaction depends on the pH of the solution and the point of zero charge (PZC) of the sorbent [199]. Modelling studies have shown that π-π interactions and H-bonding interactions play an important role in the sorption of PAHs (polycyclic aromatic hydrocarbons) [200][201][202][203]. π-π interactions are weak non-covalent interactions that influence the chemical structure by providing significant stabilisation and strengthening of the bonds.…”
Section: Sorptionmentioning
confidence: 99%